Effects of Psilocin and Psilocybin on Human 5-HT4 Serotonin and H2 Histamine Receptors in Perfused Hearts of Transgenic Mice - Pauline Braekow; Joachim Neumann; Uwe Kirchhefer; Ulrich Gergs (Pharmaceuticals)
Background/Objectives: Hallucinogenic substances such as psilocybin, psilocin, ergometrine, ergotamine, and lysergic acid diethylamide (LSD) have been demonstrated to enhance the force of contraction (FOC), in part due to the phosphorylation of phospholamban in human atrial preparations via 5-HT4 serotonin receptors and/or H2 histamine receptors. However, whether psilocybin or psilocin acts at isolated mammalian ventricular preparations and whether they increase protein phosphorylation in the mammalian ventricle remains to be elucidated. Methods: To this end, the FOC and phospholamban phosphorylation in isolated perfused hearts from transgenic mice with cardiomyocyte-specific overexpression of either human 5-HT4 receptors (5-HT4-TG) or human H2 receptors (H2-TG) and their wild-type littermates (WT) were examined. Furthermore, the ergot alkaloids ergometrine, ergotamine, and LSD were used as references. Results: Psilocybin and psilocin enhanced the FOC to 137% and to 152%, respectively, and elevated the phospholamban phosphorylation in isolated perfused hearts from 5-HT4-TG. In H2-TG hearts, psilocybin and psilocin increased the FOC to a much lesser extent but had no effect on the phospholamban phosphorylation. In contrast, LSD increased the FOC and phosphorylation state of phospholamban in isolated hearts of both 5-HT4-TG and H2-TG. On the other hand, ergometrine and ergotamine increased the FOC only in H2-TG. Ergometrine increased the phosphorylation state of phospholamban in perfused hearts from H2-TG, but not from 5-HT4-TG. Ergotamine failed to increase the phospholamban phosphorylation in both H2-TG and 5-HT4-TG. Psilocybin, psilocin, ergotamine, ergometrine, and LSD were unable to increase FOC and phospholamban phosphorylation in perfused hearts from WT. Conclusions: The increase in the phosphorylation state of phospholamban could provide a partial explanation for the positive inotropic effects and the relaxant effects of not only psilocybin and psilocin but also ergometrine and LSD in the isolated hearts of the animals used in this study.